Implementation of A Human Resource Development Model Based on Coaching in Small and Medium Pempek Businesses in Palembang City - Zaleha Trihandayani; Eni Cahyani; Usman Magaji Abdullahi; M. Naufal Hasabi Groniko (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analysis the implementation of a coaching-based human resource development model in small and medium enterprises (SMEs) producing pempek in Palembang City and to examine its effect on employee competence and performance. This research is important because human resources play a strategic role in improving the competitiveness and sustainability of SMEs, especially in traditional culinary industries. The study employed a quantitative research approach using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method for data analysis. The sampling technique used was purposive sampling, involving 200 employees from pempek SMEs who had participated in coaching or mentoring activities for at least one year. The research instrument was developed based on indicators of coaching, employee competence, empowerment, and employee performance using a Likert scale questionnaire. The results indicate that the coaching-based human resource development model has a positive and significant effect on improving employees’ skills, motivation, responsibility, communication, and collaboration within the workplace. Coaching activities also contribute to strengthening employee empowerment and improving operational performance in SMEs. Furthermore, the findings support previous studies emphasizing that coaching is an effective approach to developing human resources in small business environments characterized by informal management systems and limited organizational resources. This study provides practical implications for SME owners and government institutions in designing sustainable human resource development programs through coaching-based approaches to strengthen SME competitiveness.